Design and Analysis of Robust Multivariable PI Controller for Paper Machine Headbox Using Particle Swarm Optimisation - Saini, Parvesh; Kumar, Rajesh (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*321.17px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.955594);" role="presentation">Most of the control loops in paper machine are multivariable loops. Due to multivariable nature of the loops, <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*334.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.962408);" role="presentation">there is probability that loop have significant interaction. So, the prime objective of designing controllers for <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*347.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.924847);" role="presentation">multivariable systems is that th<span dir="ltr" style="left: calc(var(--scale-factor)*197.57px); top: calc(var(--scale-factor)*347.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.906094);" role="presentation">e process variations are minimized to get desired response. This <span dir="ltr" style="left: calc(var(--scale-factor)*458.50px); top: calc(var(--scale-factor)*347.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.872868);" role="presentation">paper <span dir="ltr" style="left: calc(var(--scale-factor)*483.58px); top: calc(var(--scale-factor)*347.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.855335);" role="presentation">presents a <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*360.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.999315);" role="presentation">multi-<span dir="ltr" style="left: calc(var(--scale-factor)*96.38px); top: calc(var(--scale-factor)*360.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.953732);" role="presentation">variable control system approach to design PI controller <span dir="ltr" style="left: calc(var(--scale-factor)*334.63px); top: calc(var(--scale-factor)*360.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.90439);" role="presentation">using <span dir="ltr" style="left: calc(var(--scale-factor)*360.07px); top: calc(var(--scale-factor)*360.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.950141);" role="presentation">Particle Swarm Optimisation <span dir="ltr" style="left: calc(var(--scale-factor)*482.98px); top: calc(var(--scale-factor)*360.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904211);" role="presentation">(PSO) <span dir="ltr" style="left: calc(var(--scale-factor)*512.02px); top: calc(var(--scale-factor)*360.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.996);" role="presentation">for <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*374.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.913497);" role="presentation">paper machine headbox. Paper machine headbox is a 2-<span dir="ltr" style="left: calc(var(--scale-factor)*301.39px); top: calc(var(--scale-factor)*374.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.946907);" role="presentation">input and 2-<span dir="ltr" style="left: calc(var(--scale-factor)*351.43px); top: calc(var(--scale-factor)*374.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.918334);" role="presentation">out<span dir="ltr" style="left: calc(var(--scale-factor)*364.15px); top: calc(var(--scale-factor)*374.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.918892);" role="presentation">put sub-<span dir="ltr" style="left: calc(var(--scale-factor)*397.51px); top: calc(var(--scale-factor)*374.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.916221);" role="presentation">process of paper machine. The <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*387.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.931366);" role="presentation">major parameters to be controlled in headbox are Total Head (Pressure) and Stock Level. <span dir="ltr" style="left: calc(var(--scale-factor)*442.66px); top: calc(var(--scale-factor)*387.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.930012);" role="presentation">The performance of <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*400.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.923013);" role="presentation">PSO based multivariable PI controller has been compared with three conventional controller tuning techniques. T<span dir="ltr" style="left: calc(var(--scale-factor)*78.26px); top: calc(var(--scale-factor)*413.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.898185);" role="presentation">he performance assessment of multivariable controllers has been done on the basis of time response, frequency <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*427.01px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.879964);" role="presentation">response, perf<span dir="ltr" style="left: calc(var(--scale-factor)*128.06px); top: calc(var(--scale-factor)*427.01px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.883721);" role="presentation">ormance indices and robustness